Simulation material for mechanical test of pressed explosive
By using simulated materials for press-load explosive mechanics tests made of ammonium sulfate, aluminum powder, microcrystalline wax, butyl rubber and graphite, the safety hazards caused by the large amount of samples for press-load explosive mechanics tests in the prior art were solved, and an effective reference for improving the safety of the test and evaluation of mechanical properties was achieved.
Patent Information
- Application Number
- CN202411711361.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-11-27
AI Technical Summary
The current technology has large samples for mechanical testing of medium-pressure explosives, which poses a large safety hazard.
The simulated material for press-load explosive mechanics tests was used, made of 65.5% ammonium sulfate, 27% to 33% aluminum powder, 1.5% to 4% microcrystalline wax, 1% to 2% butyl rubber and 0.2% to 0.8% graphite, and the drug column was made by a granulator and a pressing process was used to make the drug column.
The compressive strength and tensile strength of the drug column compressed by simulated materials are basically the same as those of the drug column compressed by polyblack aluminum-2 (JHL-2) explosives, which improves the safety of the test, reduces safety risks, and provides effective reference data for mechanical performance evaluation.
Smart Images

Figure BDA0005155810050000041 
Figure BDA0005155810050000051 
Figure BDA0005155810050000071
Abstract
Description
Technical Field
[0001] The invention relates to a simulation material for mechanical test of press-packed explosives, which is mainly suitable for aging mechanical performance evaluation, storage period evaluation and structural integrity test of mechanical test of press-packed explosives. Background Art
[0002] During the aging and structural integrity tests of press-packed explosives, a simulation material with mechanical performance parameters that are basically consistent with those of real press-packed explosives is needed to conduct relevant tests, verify the generation process of structural defects and analyze its mechanism. For example, the Chinese patent "A simulation material for polymer-based melt-cast explosive process test" with application publication number CN110470521A discloses a simulation material using a melt-cast process, which simulates the density and process viscosity of real melt-cast explosives and is mainly used in the polymer-based melt-cast explosive process test process. The Chinese patent "A simulation material for melt-cast explosive process test" with application publication number CN112048188A discloses a simulation material using a melt-cast process, which simulates the rheological characteristics and mechanical properties of real melt-cast explosives and is mainly used in the polymer-based melt-cast explosive process test process. The preparation processes of melt-cast explosives and press-packed explosives are quite different. The above two patents do not involve the simulation of press-packed explosives and the mechanical properties of press-packed explosives. Summary of the invention
[0003] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a simulation material for mechanical testing of press-packed explosives to solve the technical problem in the prior art that the large amount of samples used in mechanical testing of press-packed explosives leads to great safety hazards.
[0004] In order to solve the above technical problems, the present invention adopts the following technical solutions to achieve the above problems:
[0005] A simulation material for mechanical testing of pressurized explosives, made of the following raw materials by weight: 65.5% ammonium sulfate, 27% ~ 33% aluminum powder, 1.5% ~ 4% microcrystalline wax, 1% ~ 2% butadiene rubber, 0.2% ~ 0.8% Graphite.
[0006] The preferred embodiment of the present invention is made of the following raw materials, in parts by weight: 65.5% ammonium sulfate, 30% aluminum powder, 3% microcrystalline wax, 1.2% butadiene rubber, and 0.3% graphite.
[0007] The present invention also has the following technical features:
[0008] The aluminum powder is flaky aluminum powder or spherical aluminum powder.
[0009] The preparation process of the simulation material for mechanical test of press-packed explosives is as follows: firstly, ammonium sulfate and ethanol solvent are added into a kneading pot for infiltration and mixing, then dissolved microcrystalline wax solution and butadiene rubber solution are added for mixing, finally aluminum powder and graphite are added for uniform kneading, and the modeling powder is obtained by granulating with a granulator.
[0010] The pressing process of the simulation material for mechanical testing of pressed explosives is as follows: selecting a mold according to the size of the explosive column, weighing the mass of the molding powder according to the molding density of the explosive column, pouring the molding powder into the mold, setting the pressing pressure and holding time for pressing, demolding and trimming after completion to obtain a molded explosive column.
[0011] The medicine pressing pressure is 120MPa to 210MPa.
[0012] The mold has a diameter of 20 mm and a height of 20 mm.
[0013] The molding density of the drug column is 1.8g / cm 3 .
[0014] The pressure holding time is 3 minutes.
[0015] The tensile strength of the drug column ranges from 0.5MPa to 0.8MPa.
[0016] Compared with the prior art, the present invention has the following technical effects:
[0017] (I) The compressive strength and tensile strength of the explosive column pressed by the simulation material for mechanical test of press-packed explosives proposed by the present invention are basically consistent with those of the explosive column pressed by poly black aluminum-2 (JHL-2) explosive, which can truly reflect the change trend and change limit of strength during the mechanical test, and provide effective reference data for mechanical property evaluation, and provide more realistic and reasonable model parameters for the digital design of mechanical properties of press-packed explosives; in aging test, tensile test, mechanical compression test and dynamic Brazilian test, the explosive column pressed by the simulation material for mechanical test of press-packed explosives can avoid contact with energetic explosive components, increase the safety of the test, and reduce safety hazards.
[0018] (II) The simulation material for mechanical testing of press-packed explosives proposed in the present invention has simple composition, simple preparation process and short molding cycle, and can be reused, thereby improving work efficiency and reducing material costs. DETAILED DESCRIPTION
[0019] It should be noted that, unless otherwise specified, all raw materials in the present invention are raw materials known in the prior art.
[0020] The concept of the present invention is:
[0021] Due to its high solid content, high charge density and great power, pressurized explosives have been widely used in warhead charges of various weapons. Mechanical properties testing is required in the fields of service life evaluation, life extension, fault correction, manufacturing and weapon research and development. Therefore, it is necessary to develop a simulation material for pressurized explosive mechanical testing that can simulate the mechanical characteristics of real pressurized explosives and reduce the risks of manufacturing, storage, transportation and research processes.
[0022] In the design of simulation formula for pressed explosives, raw materials with physical properties similar to those of poly black aluminum-2 (JHL-2) explosives such as composition and density are selected, and simulation materials with mechanical properties similar to those of real explosives are designed based on material mechanical properties data and pressing process parameters. In order to facilitate aging performance research, simulation materials based on ammonium sulfate are designed, which can be recycled and convenient for waste disposal.
[0023] The cis-1,4-dimethoxy-1,4-butadiene rubber in the simulation material for mechanical test of press-packed explosives provided by the present invention is helpful to improve the plasticity of the material, and the graphite is a process aid.
[0024] In accordance with the above technical scheme, specific embodiments of the present invention are given below. It should be noted that the present invention is not limited to the following specific embodiments, and all equivalent changes made on the basis of the technical scheme of this application fall within the protection scope of the present invention.
[0025] Embodiment 1:
[0026] This embodiment provides a simulation material for mechanical testing of press-packed explosives, which is made of the following raw materials, by weight: 65.5% ammonium sulfate, 30% aluminum powder, 3% microcrystalline wax, 1.2% butadiene rubber and 0.3% graphite.
[0027] In this embodiment, the aluminum powder is flake aluminum powder.
[0028] The preparation process of the simulation material for the mechanical test of pressed explosives is as follows: first, 65.5% ammonium sulfate and ethanol solvent are added into a kneading pot for infiltration and mixing, 3% microcrystalline wax solution dissolved is added at 75°C for mixing, kneading for 10 minutes, 1.2% butadiene rubber solution is added for mixing, and finally 30% flaky aluminum powder and 0.3% graphite are added, kneading for 20 minutes, and granulating is performed by a granulator to obtain the modeling powder.
[0029] The pressing process of the simulated material for the mechanical test of pressed explosives is as follows: when pressing the explosives, a mold with a diameter of 20 mm and a height of 20 mm is used. According to the density of the explosive column of 1.8 g / cm 3 , weigh the mass of the modeling powder, pour the modeling powder into the mold, set the pressure to 150MPa, set the pressure holding time to 3min, and press it. After completion, demold and trim to obtain a formed drug column.
[0030] The performance comparison test was carried out on the explosive column pressed by the simulated material for mechanical test of the press-packed explosive prepared in this embodiment and the explosive column pressed by poly black aluminum-2 (JHL-2) explosive. The performance test was measured by the method specified in 413.1 and 416.1 of the known and public national military standard GJB772A. The performance data comparison of the test is shown in Table 1.
[0031] Table 1 Performance data comparison
[0032]
[0033] It can be seen from Table 1 that the tensile strength of the explosive column pressed by the simulated material for the mechanical test of press-packed explosives is 0.53 MPa, and the compressive strength of the explosive column pressed by the simulated material for the mechanical test of press-packed explosives is 7.25 MPa. The tensile strength and compressive strength of the explosive column pressed by the simulated material for the mechanical test of press-packed explosives are both equivalent to those of the explosive column pressed by poly black aluminum-2 (JHL-2) explosive.
[0034] Embodiment 2:
[0035] This embodiment provides a simulation material for mechanical test of press-packed explosives. The preparation process and the pressing process of the simulation material for mechanical test of press-packed explosives are basically the same as the preparation process and the pressing process disclosed in Example 1. The mass percentage composition of each component of the simulation material for mechanical test of press-packed explosives adopts the mass percentage composition of each component disclosed in Example 1. The only difference is that the pressure setting in the pressing process of the simulation material for mechanical test of press-packed explosives is different.
[0036] In this embodiment, the aluminum powder is flake aluminum powder.
[0037] In this embodiment, the pressure in the pressing process of the simulated material for the mechanical test of the press-packed explosive is set to 200 MPa.
[0038] The preparation process of the simulation material for the mechanical test of pressed explosives is as follows: first, 65.5% ammonium sulfate and ethanol solvent are added into a kneading pot for infiltration and mixing, 3% microcrystalline wax solution dissolved is added at 75°C for mixing, kneading for 10 minutes, 1.2% butadiene rubber solution is added for mixing, and finally 30% flaky aluminum powder and 0.3% graphite are added, kneading for 20 minutes, and granulating is performed by a granulator to obtain the modeling powder.
[0039] The pressing process of the simulated material for the mechanical test of pressed explosives is as follows: when pressing the explosives, a mold with a diameter of 20 mm and a height of 20 mm is used. According to the density of the explosive column of 1.8 g / cm 3 , weigh the mass of the modeling powder, pour the modeling powder into the mold, set the pressure to 200MPa, set the pressure holding time to 3min, and press it. After completion, demold and trim to obtain a formed drug column.
[0040] The performance comparison test was carried out on the explosive column pressed by the simulated material for mechanical test of the press-packed explosive prepared in this embodiment and the explosive column pressed by the poly black aluminum-2 (JHL-2) explosive. The performance test was measured by the method specified in 413.1 and 416.1 of the known and public national military standard GJB772A. The performance data comparison of the test is shown in Table 2.
[0041] Table 2 Performance data comparison
[0042]
[0043] As shown in Table 2, the tensile strength of the explosive column pressed by the simulated material for the mechanical test of the press-packed explosive is 0.60MPa, and the compressive strength of the explosive column pressed by the simulated material for the mechanical test of the press-packed explosive is 7.55MPa. The tensile strength and compressive strength of the explosive column pressed by the simulated material for the mechanical test of the press-packed explosive are both comparable to those of the explosive column pressed by the poly black aluminum-2 (JHL-2) explosive. Compared with the 150MPa set in the pressure of the press process in Example 1, when the pressure of the press process in this embodiment is set to 200MPa, the tensile strength and compressive strength of the explosive column pressed by the simulated material for the mechanical test of the press-packed explosive are both improved.
[0044] Embodiment 3:
[0045] This embodiment provides a simulation material for mechanical test of press-packed explosives, and the preparation process and the pressing process of the simulation material for mechanical test of press-packed explosives are basically the same as the preparation process and the pressing process disclosed in Example 1, and the mass percentage composition of each component of the simulation material for mechanical test of press-packed explosives adopts the mass percentage composition of each component disclosed in Example 1. The difference lies in the different forms of aluminum powder in the preparation process of the simulation material for mechanical test of press-packed explosives and the different pressure settings in the pressing process of the simulation material for mechanical test of press-packed explosives.
[0046] In this embodiment, the aluminum powder is spherical aluminum powder.
[0047] In this embodiment, the pressure in the pressing process of the simulated material for the mechanical test of the press-packed explosive is set to 200 MPa.
[0048] The preparation process of the simulation material for the mechanical test of pressed explosives is as follows: first, 65.5% ammonium sulfate and ethanol solvent are added into a kneading pot for infiltration and mixing, 3% microcrystalline wax solution dissolved is added at 75°C for mixing, kneading for 10 minutes, 1.2% butadiene rubber solution is added for mixing, and finally 30% spherical aluminum powder and 0.3% graphite are added, kneading for 20 minutes, and granulating is performed by a granulator to obtain the modeling powder.
[0049] The pressing process of the simulated material for the mechanical test of pressed explosives is as follows: when pressing the explosives, a mold with a diameter of 20 mm and a height of 20 mm is used. According to the density of the explosive column of 1.8 g / cm3 , weigh the mass of the modeling powder, pour the modeling powder into the mold, set the pressure to 200MPa, set the pressure holding time to 3min, and press it. After completion, demold and trim to obtain a formed drug column.
[0050] The performance comparison test was carried out on the explosive column pressed by the simulated material for mechanical test of the press-packed explosive prepared in this embodiment and the explosive column pressed by the poly black aluminum-2 (JHL-2) explosive. The performance test was measured by the method specified in 413.1 and 416.1 of the known and public national military standard GJB772A. The performance data comparison of the test is shown in Table 3.
[0051] Table 3 Performance data comparison
[0052]
[0053] As shown in Table 3, the tensile strength of the explosive column pressed by the simulated material for mechanical test of press-packed explosives is 0.71MPa, and the compressive strength of the explosive column pressed by the simulated material for mechanical test of press-packed explosives is 7.72MPa. The tensile strength and compressive strength of the explosive column pressed by the simulated material for mechanical test of press-packed explosives are both comparable to those of the explosive column pressed by poly black aluminum-2 (JHL-2) explosive. Compared with the flaky aluminum powder used in the preparation process of the simulated material for mechanical test of press-packed explosives in Example 2, the spherical aluminum powder used in this example improves the tensile strength and compressive strength of the explosive column pressed by the simulated material for mechanical test of press-packed explosives.
Claims
1. A simulation material for mechanical testing of press-packed explosives, characterized in that: In parts by weight, it is made from the following raw materials: 65.5% ammonium sulfate, 27% ~ 33% aluminum powder, 1.5% ~ 4% microcrystalline wax, 1% ~ 2% butadiene rubber, 0.2% ~ 0.8% Graphite.
2. The simulation material for mechanical testing of press-packed explosives according to claim 1, characterized in that: The invention is prepared from the following raw materials by weight: 65.5% ammonium sulfate, 30% aluminum powder, 3% microcrystalline wax, 1.2% butadiene rubber and 0.3% graphite.
3. The simulation material for mechanical testing of press-packed explosives according to claim 1, characterized in that: The aluminum powder is flaky aluminum powder or spherical aluminum powder.
4. The simulation material for mechanical testing of press-packed explosives according to claim 1, characterized in that: The preparation process of the simulation material for mechanical test of press-packed explosives is as follows: firstly, ammonium sulfate and ethanol solvent are added into a kneading pot for infiltration and mixing, then dissolved microcrystalline wax solution and butadiene rubber solution are added for mixing, finally aluminum powder and graphite are added for uniform kneading, and the modeling powder is obtained by granulating with a granulator.
5. The simulation material for mechanical testing of press-packed explosives according to claim 1, characterized in that: The pressing process of the simulation material for mechanical testing of pressed explosives is as follows: selecting a mold according to the size of the explosive column, weighing the mass of the molding powder according to the molding density of the explosive column, pouring the molding powder into the mold, setting the pressing pressure and holding time for pressing, demolding and trimming after completion to obtain a molded explosive column.
6. The simulation material for mechanical testing of press-packed explosives according to claim 5, characterized in that: The medicine pressing pressure is 120MPa to 210MPa.
7. The simulation material for mechanical testing of press-packed explosives according to claim 5, characterized in that: The mold has a diameter of 20 mm and a height of 20 mm.
8. The simulation material for mechanical testing of press-packed explosives according to claim 5, characterized in that: The molding density of the drug column is 1.8g / cm 3 .
9. The simulation material for mechanical testing of press-packed explosives according to claim 5, characterized in that: The pressure holding time is 3 minutes.
10. The simulation material for mechanical testing of press-packed explosives according to claim 5, characterized in that: The tensile strength of the drug column ranges from 0.5MPa to 0.8MPa.
Citation Information
Patent Citations
Simulation material for cast explosive process test
CN112048188A
Casting-curing insensitive high-explosion-heat explosive and preparation method thereof
CN103073369A
Insensitive pressed explosive passing slow cook-off test
CN106588520A
High energy insensitive press-fitting high polymer bonded explosive
CN107879867A
Technology for pressing explosive column with preset density gradient
CN108484340A
Cited By
Equivalent substitute for mechanical property test of hexogen-based aluminum-free press-fitting explosive under temperature load as well as preparation method and application of equivalent substitute
CN121632725A
Equivalent substitute for testing mechanical properties of rdx-based non-aluminum press-pack explosive under temperature load, preparation method and application thereof
CN121632725B